Oxysterol-Binding Protein 2 Promotes Pancreatic Ductal Adenocarcinoma Progression Through Epithelial-Mesenchymal Transition - Huang, Shuai; Zhang, Xudong; Luo, Kai; Jiang, Li; Jiang, Jianhua; Li, Renfeng (Frontiers in Oncology, 2022)
Oxysterol-binding protein 2 (OSBP2) is crucial for promoting the growth and development of cancers; however, its effects on pancreatic ductal adenocarcinoma (PDAC) are still unclear. Here, we report that OSBP2 is an efficient tumour-associated protein to lead to extremely malignant characteristics in PDAC. We discovered that increased OSBP2 expression in primary tumours was associated with shorter survival in PDAC patients. Therefore, we used immunohistochemistry (IHC) to analyse the levels of OSBP2 expression in PDAC tissues and adjacent paracancerous tissues. We used wound healing and Transwell assays to evaluate the effects of OSBP2 on PDAC cell (ASPC-1 and BXPC-3) migration and invasion, respectively, and CCK-8 and Annexin V/PI double staining to evaluate the effects of OSBP2 on PDAC cell proliferation and apoptosis, respectively. Western blotting was used to analyse the effect of OSBP2 on the PDAC cell phenotype. We also explored the effect of OSBP2 on chemosensitivity to gemcitabine (GEM) and 5-fluorouracil (5-FU). We validated these findings in an in vivo mouse model. The data show that OSBP2 overexpression promoted PDAC cell migration, invasion, proliferation and chemotherapy resistance and decreased apoptosis. OSBP2 overexpression downregulated E-cadherin expression and upregulated N-cadherin, vimentin, Snail, Slug, ZEB1 and β-catenin expression. Taken together, our findings indicated that OSBP2 was overexpressed in PDAC and that upregulation of OSBP2 may promote PDAC progression. Therefore, OSBP2 may have potential diagnostic and therapeutic value in PDAC.